CONFRONTING THE CHALLENGE OF DIABETIC CYSTOPATHY WITH ESBL KLEBSIELLA PNEUMONIAE UROSEPSIS: A COMPLEX CLINICAL CONUNDRUM - Hatta, Siti Nabihah Mohamed; Bahrudin, Mohd Fyzal (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The multisystemic nature of diabetes mellitus (DM) also affects the bladder causing diabetic cystopathy (DC), especially in middle-aged or elderly patients with longstanding poorly controlled disease, and it carries an increased risk of urinary tract infections (UTI). CASE A 54-year-old female with a background of poorly controlled DM Type 2 (HbA1c 14%) and multiple target organ damage including HF, IHD and retinopathy, presented with chronic urinary frequency and a 3-day history of fever and dysuria. Upon arrival at the hospital, she was in septic shock. Investigations revealed leukocytosis with CRP of 104 mg/L and procalcitonin of 2.24ng/ml. Her urinalysis revealed UTI, but the urine culture was negative. Subsequently, blood culture revealed growth of extendedspectrum beta-lactamase (ESBL) Klebsiella pneumoniae. Abdominal ultrasound revealed thickened and trabeculated urinary bladder wall. She was referred to urology and uroflow done showed a low average flow of 7.7ml/s and a high post-void residual of 180 ml suggestive of DC. In the ward, she improved after receiving intravenous Ceftriaxone for 3 days followed by Augmentin for 14 days. The pathogenesis of DC is multifactorial. It may be secondary to autonomic neuropathy beginning with impaired bladder sensation and progressing to impaired contractility and urinary retention. Other theories involve alterations in detrusor muscle physiology and urothelial dysfunction. Those patients may be asymptomatic or may have variable voiding complaints such as overactive bladder, urge incontinence and overflow incontinence. Urodynamic evaluation is the cornerstone of diagnosis characterized by lower flow rates and higher post-void residual volumes. Patients with DM are at an increased risk of developing UTI due to impaired immune function and poor metabolic control aggravated by DC which can be further complicated by the emergence of resistant pathogens and lead to poor outcomes. CONCLUSION Proper management of DM is crucial in preventing complications such as DC and improving overall health outcomes.